ANALISIS KOHESI GRAMATIKAL DAN LEKSIKAL DALAM NOVEL “THE BOOK OF ALMOST” KARYA BRIAN KHRISNA - Anggun Sita Dewi; Atiqa Sabardila (Universitas Batanghari, 2023)
This study aims to (1) describe the analysis of grammatical cohesion in the novel